Load capacity of hybrid precast column - Ong, Hui Choon. (2008)
The main objective of this research is to evaluate the behaviour of hybrid precast columns that are formed by embedding structural steel column section at the ends of precast concrete columns. The purpose of this project is also to investigate the factors that govern the load transfer mechanisms from the embedded structural steel section into the reinforced concrete section of the hybrid column.